Using the PBIS Framework to Meet the Mental Health Needs of Youth in Juvenile Justice Facilities. (April 2020) - Kumm, Skip; Mathur, Sarup R.; Cassavaugh, Michelle; Butts, Erin
Youth in juvenile justice facilities may experience symptoms of mental health disorders and trauma at a higher rate than their normative peers. As a result, juvenile justice facilities have become de facto mental health agencies, resulting in an increased need to provide interventions that can meet the various needs of their residents. Embedding mental health and trauma-informed care into tiered facility-wide positive behavioral interventions and supports (FW-PBIS) is an emerging practice to meet a multitude of youth mental health symptoms. In this article, we provide examples of how mental health and trauma-informed care can be interwoven into an FW-PBIS framework by using a data-based decision-making process to guide the implementation of tiered evidence-based interventions, and we offer implications for practice and research.